Human resource management : linking strategy to practice - Stewart, Greg L.; Brown, Kenneth G., 1969- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2011)
Stewart and Brown's Human Resource Management: Linking Strategy to Practice 2e is designed to help students understand traditional human resource concepts within a decision-making framework. Throughout the book, the authors emphasize how organizations excel when they have consistent human resource practices that align with their strategic direction. The strategic perspective is critical for both business and management majors, since most will work as managers with the charge to lead and direct others. Understanding the strategic benefits of good human resource management can help future managers better secure and motivate talented employees. -- from http://eu.wiley.com (Sep. 29, 2011).
PART I. Seeing People as a Strategic Resource. 1. Creating Value Through Human Resources --- 2. Making Human Resource Management Strategic --- 3. Ensuring Equal Employment Opportunity and Safety ---- PART II. Securing Effective Employees. 4. Designing Productive and Satisfying Work --- 5. Recruiting Talented Employees --- 6. Selecting Employees Who Fit --- 7. Managing Employee Retention and Separation. ---- PART III. Improving Employee Performance. 8. Measuring Performance and Providing Feedback --- 9. Training for Improved Performance --- 10. Developing Employees and Their Careers ---- PART IV. Motivating and Managing Employees. 11. Motivating Employees Through Compensation --- 12. Designing Compensation and Benefit Packages --- 13. Working Effectively with Labor --- 14. Aligning Strategy with Practice ---- APPENDICES. A. Occupational Outlook for HR Managers and Specialists --- B. Human Resource Certification Institute Bodies of Knowledge --- C. Human Resource Planning Society Knowledge Areas --- D. Major Employment Laws in the United States --- E. Organizations of Interest to HR Students and Professionals --- F. Journals Useful to HR Students and Professionals.
Previous ed.: 2009.
Includes bibliographical references and indexes.
Keywords: Personnel management